Oxytocin varies across the life course in a sex-specific way in a human subsistence population - Abigail E. Colby; Dominik C. Jud; Valerie Baettig; Jordan S. Martin; Camila Scaff; Michael D. Gurven; Benjamin C. Trumble; Bret A. Beheim; Paul L. Hooper; Daniel K. Cummings; Hillard Kaplan; Jonathan Stieglitz; et al. (Proceedings of the National Academy of Sciences, 2025)
Oxytocin, a hormone linked to reproduction and health, may mediate life-history trade-offs across the human life course. Yet, how oxytocin naturally varies with age remains poorly understood. Here, working with the Tsimane, forager-horticulturalists of lowland Bolivia, we collected the largest sample of oxytocin measurements to date (n = 1,242 samples, n = 405 individuals, age = 2 to 84 y, 51% female), and i) examined how oxytocin varies throughout the life course in females and males, and ii) investigated potential drivers of age- and sex-specific variation. Our sample provides rare insight into the relationship between oxytocin and age in a context where energy is limited and trade-offs between reproduction and somatic maintenance are more salient. We found that oxytocin follows a nonlinear sex-specific trajectory throughout the life course. In females, oxytocin levels were high during the reproductive years and declined in the early to midforties, a pattern largely explained by breastfeeding and, to a lesser extent, childcare and good self-rated health. In males, oxytocin was low in early adulthood but high in old age, and although higher oxytocin was linked to good self-rated health, this did not explain the rise in oxytocin in later life. These findings suggest that oxytocin is instrumental for reproduction and caregiving in females and may also be associated with health in both males and females. Together, our work highlights oxytocin’s broader biological significance across the human life course, suggesting that it may play a pivotal role in coordinating age- and sex-specific trade-offs involving reproduction and health.